2009
DOI: 10.1007/s10620-009-0744-1
|View full text |Cite
|
Sign up to set email alerts
|

Moexipril for Treatment of Primary Biliary Cirrhosis in Patients with an Incomplete Response to Ursodeoxycholic Acid

Abstract: Blockade of angiotensin II synthesis attenuates hepatic fibrosis in different experimental models of chronic liver injury. We evaluated the safety and efficacy of moexipril, an angiotensin-converting enzyme inhibitor, in patients with primary biliary cirrhosis (PBC) who have had a suboptimal response to ursodeoxycholic acid (UDCA). Twenty PBC patients on UDCA (13-15 mg/kg/day) therapy with an elevation of serum alkaline phosphatase at least twice the upper limit of normal were treated with oral moexipril 15 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
(74 reference statements)
1
9
0
Order By: Relevance
“…Candesartan and ursodeoxycholic acid in combination led to histological improvement in fibrosis compared to ursodeoxycholic acid alone [44]. Both ACEi and ARB decreased portal pressure in cirrhosis in one study, while in others no such effect was demonstrated [45][46][47][48]. Previous data have shown that ACEi have several effects inhibiting HSC activation, decreasing portal hypertension and slowing fibrosis progression by reducing the effect of angiotensin II on the activity and proliferation of hepatic stellate cells [9,45,[49][50][51][52].…”
Section: Discussionmentioning
confidence: 92%
“…Candesartan and ursodeoxycholic acid in combination led to histological improvement in fibrosis compared to ursodeoxycholic acid alone [44]. Both ACEi and ARB decreased portal pressure in cirrhosis in one study, while in others no such effect was demonstrated [45][46][47][48]. Previous data have shown that ACEi have several effects inhibiting HSC activation, decreasing portal hypertension and slowing fibrosis progression by reducing the effect of angiotensin II on the activity and proliferation of hepatic stellate cells [9,45,[49][50][51][52].…”
Section: Discussionmentioning
confidence: 92%
“…In ALD patients, a combination of the ARB candesartan and ursodeoxycholic acid (UDCA) improved the patient's fibrosis scores compared to UDCA treatment alone (110). However since other clinical trials did not show any effect, more studies are needed to prove the efficacy of RAS antagonists in hepatic fibrosis (111,112).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Finally, Ang II also contributes to the oxidative stress in the fibrotic liver. Therefore, Ang II and its interaction with AT1-R are considered to play an important role in liver fibrogenesis and its blocking by ACE inhibitors (ACEi) or AT1-R blockers (ARBs) may be an effective therapeutic option for treatment of liver fibrosis and they are already in clinical trials, for example, Losartan [71], Irbesartan [72], and Candesartan and Moexipril [73] (Table 1). Losartan, Irbesartan, and Candesartan share similarities in the chemical structure and they all are AT1-R blockers, in contrast to Moexipril, which is an ACE inhibitor.…”
Section: Developments In Targeted Therapy Related To Liver Fibrosismentioning
confidence: 99%
“…However, long-term treatment with Irbesartan (ARB and antihypertensive drug) in severe fibrosis with chronic hepatitis C showed no substantial improvement in fibrosis scores, arterial pressure, and organ stiffness in the treated group, despite the fact that treatment was safe and well tolerated [72]. In addition, ACE inhibitor Moexipril treatment did not show beneficial effects in primary biliary cirrhosis patients [73]. Furthermore, in HALT-C cohort study, ACEi/ARB therapy did not retard the progression of fibrosis [76].…”
Section: Developments In Targeted Therapy Related To Liver Fibrosismentioning
confidence: 99%